Protective effects of Fraxinus xanthoxyloides bark in alloxan-induced diabetic rats: A phytochemical and pharmacological approach - Mashal Shahzadi; Tahira Younis; Ayman M. Al-Qaaneh; Ali Raza Ishaq; Farah Deeba; Musrat Shaheen; Mostafa A. Abdel-Maksoud; Saeedah Almutairi; Abdulaziz Alamri; Heba A. S. El-Nashar (PLoS ONE, 2026)
Fraxinus xanthoxyloides Wall. ex DC (Family-Oleaceae) is a tiny tree found in arid highlands, often referred to as “Afghan ash”. This study aimed to explore F. xanthoxyloides bark extract as a potential anti-diabetic agent by conducting GC-MS analysis along with in vitro and in vivo studies. F. xanthoxyloides bark methanol extract (FXBM) was fractionated with n-hexane (FXBH), followed by chloroform (FXBC), ethyl acetate (FXBE), and residual aqueous fraction (FXBA). GC-MS and HPLC-MS analysis of the total extract were performed. The inhibitory activities against α-amylase, α-glucosidase, and DPP4 were assessed for the extract and its fractions. The in vivo study included five groups: control group, diabetic control, groups pretreated with alloxan (150 mg/kg) + glibenclamide (5 mg/kg), group pretreated with alloxan (150 mg/kg) + FXBH (200 mg/kg), and group pretreated with alloxan (150 mg/kg) + FXBH (400 mg/kg). Further, a histopathological investigation was conducted. GC-MS analysis of FXBM revealed the presence of 17 compounds predominated by esters (17.9%), polyols (16.35%), and O -glycosides (12.24%). Among all extract/fractions, FXBH showed maximum α-amylase, α-glucosidase, and DPP4 inhibition when compared to acarbose and berberine, respectively. It also achieved the highest glucose uptake among all extract/fractions when compared with metformin. HPLC-DAD analysis showed the presence of gallic acid (3.29 µg/mg), catechin (4.23 µg/mg), caffeic acid (6.05 µg/mg), ferulic acid (2.99 µg/mg), and quercetin (6.4 µg/mg). FXBH-treated rats showed a significant increase in body weight and reduced blood glucose levels ( p < 0.05) from days 1–30. The biochemical parameters like triglyceride, low-density lipoprotein, cholesterol, lipase, amylase, C-reactive protein, alanine aminotransferase, aspartate aminotransferase, creatinine, HbA1c, and urea were decreased, while high-density lipoprotein was elevated, compared to diabetic control. Histopathological studies demonstrated restoration of pancreatic β-cells. In conclusion, F. xanthoxyloides bark extract exhibited potential antidiabetic effects; meanwhile, further studies are recommended to characterize the pharmacodynamics, pharmacokinetics, and synergistic effects with standard drugs.